FORMULATION AND ANTIOXIDANT ACTIVITY FACE TONER BUTTERFLY PEA FLOWER KOMBUCHA (Clitoria ternatea L.) WITH DPPH METHOD - Rizikiyan, Yayan; Hidayat, Salsabila Aulia; Suharyani, Ine; Sulastri, Lela; Indriaty, Sulistiorini; Karlina, Nina (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Antioxidants can be given to the skin through cosmetics such as face toners. One source of antioxidants is obtained through the fermentation of butterfly pea flower kombucha (Clitoria ternatea L.), which has been proven to have better antioxidant activity than butterfly pea flower extract alone. This study aimed to determine the metabolite compounds in butterfly pea flower kombucha and create a facial toner formulation with good antioxidant activity. The butterfly pea flower kombucha was fermented for 6 days at room temperature. Facial toners were made with concentrations of 5%, 7,5% and 10%. Evaluation of the face toner includes organoleptic, homogeneity, pH, specific gravity, and viscosity tests. The antioxidant activity test used the DPPH (1,1-diphenyl-2-pycrilhydrazil) method, with vitamin C as a positive control. The results showed that there were alkaloids, flavonoids, saponins, and terpenoid compounds in butterfly pea flower kombucha. Face toners with concentrations of 5%, 7.5%, and 10% could be prepared and met all evaluations (organoleptic tests, homogeneity, pH, specific gravity, and viscosity). Antioxidant test results on formula 1 IC50 50,21±SD 0,01 (strong), formula 2 IC50 44,32±SD 0,02 (very strong) and formula 3 IC50 38,62±SD 0,03 (very strong). The higher the concentration of butterfly pea flower kombucha, the higher the antioxidant activity. Butterfly pea flower kombucha (Clitoria ternatea L.) which is formulated as a face toner preparation has strong to very strong antioxidants, and the increasing concentration of active ingredients had an effect on antioxidant activity.  Keywords: face toner, butterfly pea flower kombucha, DPPH method, antioxidant activity